Pengaruh Motivasi Kerja Dan Iklim Organisasi Terhadap Prestasi Kerja Pegawai Pada Balai Penjaminan Mutu Pendidikan Provinsi Maluku - Nia Saniansih; Mohamad A. Rahawarin; Jeanly Waisapy (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
This research is a quantitative type of research. Aims to determine the influence of Work Motivation and Organizational Climate on Employee Work Performance at the Maluku Provincial Education Quality Assurance Center. The sample in this study was 44 respondent. The data collection techniques used are observations, questionnaires using multiple linear regression analysis models and classical assumption tests. The results of this study showed that the influence of work motivation on employee work performance partially contributed effectively by 53.1%. The influence of the organizational climate on work performance partially contributed effectively by 43.3%. Simultaneously, work motivation and organizational climate contributed effectively 28.7% to employee work performance and 71.3% were influenced by other variables that were not studied by researchers.